2022
DOI: 10.1098/rspa.2022.0474
|View full text |Cite
|
Sign up to set email alerts
|

Solitons on the rarefaction wave background via the Darboux transformation

Abstract: Rarefaction waves and dispersive shock waves are generated from the step-like initial data in many nonlinear evolution equations including the classical example of the Korteweg–de Vries (KdV) equation. When a solitary wave is injected on the step-like initial data, it is either transmitted over or trapped inside the rarefaction wave background. We show that the transmitted soliton can be obtained by using the Darboux transformation for the KdV equation. On the other hand, we show with the help of numerical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…has recently been shown that the spectrum for the trapped, pseudosoliton for the soliton-RW interaction is identified by a resonant pole in the complex plane. 27 There are a number of implications of Equation ( 82), which we now investigate. First, we need to distinguish between where the soliton center 𝑥 0 is initialized.…”
Section: Soliton-rw Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…has recently been shown that the spectrum for the trapped, pseudosoliton for the soliton-RW interaction is identified by a resonant pole in the complex plane. 27 There are a number of implications of Equation ( 82), which we now investigate. First, we need to distinguish between where the soliton center 𝑥 0 is initialized.…”
Section: Soliton-rw Interactionmentioning
confidence: 99%
“…In Section 4, we confirm by IST analysis that λ 0 defined in () for soliton–RW and soliton–DSW interaction from modulation theory is precisely the proper eigenvalue for a genuine soliton solution or a pseudoembedded eigenvalue when a genuine soliton solution does not exist. It has recently been shown that the spectrum for the trapped, pseudosoliton for the soliton–RW interaction is identified by a resonant pole in the complex plane 27 …”
Section: Whitham Modulation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…When a soliton becomes embedded or trapped within a DSW, the trapped soliton resembles a depression (dark) nonlinear wavepacket. Similar transmission and trapping scenarios were analyzed for solitons interacting with rarefaction waves [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interaction between an individual (tracer) soliton and a large-scale coherent nonlinear structure such as rarefaction and dispersive shock wave has been studied both theoretically and experimentally [22][23][24][25][26][27][28]. The trajectory of the tracer soliton within these macroscopic nonlinear structures is directed by the structure's mean field, which results either in the trapping of the soliton inside or its transmission (tunneling) through the large-scale nonlinear wave.…”
mentioning
confidence: 99%